THE AGENTS ROLE TO CREATE E-LOYALTY - Albetris, Albetris; Johannes, Johannes; Octavia, Ade; Aurora Lubis, Tona (Dinasti Publisher, 2022)
Competition in banking services such as branchless banking, the use of technological facilities and/or involving third party services, especially to serve the unbanked/unbanked community, has great potential to expand the distribution of financial services to the public. Models of service marketing (service marketing), relationship marketing (relationship marketing) and digital marketing (digital marketing) need to be studied simultaneously through a banking service marketing management approach to obtain electronic loyalty. The purpose of this study is to obtain an agent electronic loyalty model at state banks that provide branchless banking as marketing strategy for banking services, especially branchless banking in Jambi. The research design used an explanatory survey approach. The survey was conducted on agents at state banks that operate branchless banking in Jambi. respondents was 392 agents who were taken by multistage random sampling. Data analysis was carried out using a structural equation modeling (SEM) approach and SmartPLS 4.0 program.